Naringenin protects against acute pancreatitis-associated intestinal injury by inhibiting NLRP3 inflammasome activation via AhR signaling - Yan, Xu; Lin, Tianjiao; Zhu, Qingyun; Zhang, Yushi; Song, Zhimin; Pan, Xinting (Frontiers in Pharmacology, 2023)
Background: The current study examined the functions and mechanisms for how naringenin protects against SAP-related intestinal injury by modulating the AhR/NLRP3 signaling pathway. Material and methods: Fifteen healthy male C57BL/6 mice were randomly divided into SAP (n=12) and normal (n=3) groups. Mice in the SAP group received caerulein and lipopolysaccharide intraperitoneal injection and then randomly assigned to SAP, NAR, CH223191, and DEX groups. The pathological changes of pancreatic and intestinal mucosa showed by H&E staining. In vitro, RAW264.7 cells were exposed to lipopolysaccharide and treated with naringenin. The levels of NLRP3, AhR, IL-1β, TNF-α, and IL-6 of the SAP model and RAW264.7 cells were evaluated by enzyme-linked immunosorbent assay, quantitative Real-Time PCR, western blot, and immunohistochemistry. And the nuclear translocation of AhR was shown by immunofluorescence. AutoDockTools was used to predict the conformations of naringenin-AhR binding and PyMol 2.4 was used to visualize them. Results: The pancreatic and intestinal injury of mice was alleviated by treatment with naringenin. Naringenin inhibited the activation of the NLRP3 inflammasome and inhibited the damage of the intestinal tight junction. Moreover, naringenin increased AhR nuclear translocation and activated the AhR pathway. Conclusion: Naringenin can reduce SAP-associated intestinal injury by inhibiting the activation of NLRP3 inflammasome via the AhR signaling pathway.